A Review on Performance Comparison and Clinical Selection Strategies of Dental Restorative Materials - Meng, Fei; Chen, Yang (International Journal of Materials Science and Technology Studies, 2025)
Dental restoration for tooth defects is a crucial part of oral clinical practice, and the selection of restorative materials directly affects the long-term success rate of restorations. This article systematically compares the mechanical properties, biocompatibility, aesthetic effects, and operability of currently commonly used dental restorative materials (including composite resins, glass ionomer cements, ceramic inlays, metal alloys, etc.). Based on evidence-based medical evidence, clinical selection strategies for different types of defects, tooth positions, and patient needs are proposed, providing scientific decision-making basis for oral physicians.